Effect Effect of Different Forages and Concentrates Balance in Complete Feeds on In Vitro the Digestibility of Crude Fat and Extractable Material Without Nitrogen - Ridhasmara, Arum Pidie; Suryapratama, Wardhana; Susanti, Emmy (Fakultas Peternakan Universitas Jenderal Soedirman, 2024)
ARUM PIDIE RIDHASMARA. The aim of the study was to examine the effect of different forage and concentrate balances on crude fat digestibility and BETN in vitro. Experimental research using a completely randomized design (CRD) with 3 treatments and 6 replicates. The treatments consisted of P1: 30% forage + 70% concentrate + 0.01 organic chromium; P2: 50% forage + 50% concentrate + 0.01 organic chromium; P3: 70% forage + 30% concentrate + 0.01 organic chromium. The results of the analysis showed that the digestibility of crude fat in P1 (30% forage and 70% concentrate) with P2 (50% forage and 50% concentrate) was not significantly different compared to P3 (70% forage and 30% concentrate) but P1 with P3 showed a significant difference (P <0.05). The analysis showed that BETN digestibility in P1 (30% forage and 70% concentrate) with P2 (50% forage and 50% concentrate) showed no significant difference. P2 with P3 (70% forage and 30% concentrate) showed a significant difference (P<0.01), while P1 with P3 showed a very significant difference (P<0.01). In conclusion, the test results proved that every decrease, the digestibility value of crude fat will increase and the BETN digestibility value of material will be smaller